Isotope and elemental geochemistry of human hair from the United States - Brett James Tipple; Thuan H Chau; Lesley A Chesson; James Russell Ehleringer; Christy J Mancuso; Luciano O Valenzuela (PANGAEA, 2023)
Hair samples were collected throughout the United States, with particular focus on major metropolitan areas of the western United States. Hair samples were collected in 2004 as well as between 2013-2015. Here hydrogen (d2H) and oxygen (d18O) isotope values along with strontium isotope ratios (87Sr/86Sr) and element abundances were measured. d2H and d18O values, 87Sr/86Sr, and elemental compositions of 560, 385 and 306 hair samples were analyzed following Tipple et al., 2018 (Scientific Reports, 8, 2224), respectively. The purpose of these data was to assess geospatial variations in isotope and elemental geochemistry of human hair. We found that the isotope and elemental geochemistry of human hair largely corresponded to the geochemistry of drinking and bathing water, which in turn varied by water source and management practice. These data provide a foundation to reconstruct human movements using the geochemistry of modern or ancient human hair.